A Novel Graphene-Supported Palladium Catalyst for Suzuki–Miyaura Coupling of Less Reactive Heteroaryl Halides in Water - Abu, Taher; Lee, Dong-Jin; Lee, Ik-Mo; Lutfor, M. R.; Sarkar, Shaheen M. (Korean Chemical Society, Seoul & Wiley-VCH, 2016)
An efficient reduced graphene oxide-supported heterogenized palladium complex with pyrene-tagged ketoiminato ligand has been developed and used for cross-coupling of less reactive heteroaryl halides in water. Desirable catalytic activity was observed with high (up to 98%) conversion of the less reactive reactants under relatively mild conditions. The efficiency and green nature of the catalyst were confirmed without significant loss of activity.